“Covering the Field” In Justice System: The Ethical Foundation for Reliance on Scientific and Technologically Driven Justice Delivery - Nyeenenwa, Stephen (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
The hallmark of a good justice delivery system is one that is unbiased, fast, timely, impartial and efficient in the determination of issues brought to court. “Justice delayed is justice denied” is an assertion that places emphasis on why the courts should be a timely, effective and efficient arbiter of cases brought before them occasioned by its delivery of the final verdict. The court cannot perform magic, because they depend on the working tools and materials its disposal in the adjudication of disputes. Over the years, we have come to know that the problems that bedevil our judiciary system are enormous, and include the massive backlog of cases, poor maintenance of e-courts records, the judiciary’s non digitalisation, partiality, an unsavoury harvest of needless delaying interlocutory appeals, executive interference, disobedience to court orders and lack of total independence of the judicial arm of government. We are similarly aware of the damaging effects caused by poor case management, legal research, document automation, online dispute resolution, access to justice, legal analytics, e-discovery, e-filing, artificial-enabled referencing and online hearings. I will in this article seek to unravel how the courts and security agencies can successfully harness technological innovations in overcoming and resolving the intractable ills that have for long dogged the judiciary. Such ills include because I believe that deploying an adequate data-based planning and safeguards, technological tools can be a game changer. This paper knows and takes these problems as given, hence I am minded to examine the ethical foundation in support of the court’s reliance on scientific and technologically driven justice, especially, with the explosion in the evolution and utility of science, technology and the all-pervasive artificial intelligence. The ethical application of scientific, technological and artificial intelligent (AI) tools in crime investigation, court and criminal administration is what is needed to translate into covering the field in justice delivery in Nigeria. This is what will bring out the true meaning of justice, justice for the both parties, and justice for the Courts. We conclude that the introduction and statutory validation of the utilisation of scientific and technological tools in the administration of justice would deliver to us a holistic overhaul of the judicial system, covering the initiation, hearing and quick determination of cases by the courts.